Effect of pruning height and organic fertilization on the morphological and productive characteristics of Moringa oleifera Lam. in the Peruvian dry tropics - Yalta Vela, Juan (2024)
The objective of the study was to evaluate the effect of pruning height (PH) and organic fertilization dose (FD) on the morphology and productive characteristics of Moringa oleifera Lam. We germinated seeds collected from 10-year-old shrubs, and 2-month-old seedlings were transplanted in the final field. We used a two-factor design of PH (PH1:0.4, PH2:0.8, and PH3:1.2m from the ground) and FD (FD0:0, FD1:500, FD2:750, and FD3:1,000 g of decomposing goat manure). We carried out an initial pruning 4 months after transplanting and the harvests every 45 days. After three consecutive harvests, PH3 improved N° branches (12.53 ± 3.09) and dry matter (21.98 ± 1.30%), but PH1 showed greater stem lengths (1.65 ± 0.24 m) (p < 0.01). There was no difference in the stems and leaf weights between PH2 and PH3, and no trait varied according to FD (p > 0.05). The PH × FD interaction can improve the plant diameter (p < 0.01) and dry matter (p < 0.05) with PH2 (56.79 ± 3.71 mm) and PH3 (23.20 ± 1.04%) from FD1. We found an increasing trend in N° branches, plant diameter (p < 0.01), and the leaf–stem ratio. However, in the third harvest, the biomass production trend was downward for a short period for an adequate replacement of nutrients from the incorporated organic fertilizer. It is recommended to prune M. oleifera at 1.2m from the ground to stimulate greater biomass and maintain the leaf–stem ratio throughout the evaluated harvests and apply more than 500 g of goat manure after each harvest to restore the nutrients extracted from the soil.